Peningkatan Kualitas Pembelajaran Seni Budaya melalui Pengembangan Kreativitas Siswa Berbasis Lingkungan - Idea Kartika Septarina; Binti Maunah (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) UIN Sayyid Ali Rahmatullah Tulungagung, 2015)
The purpose of this study is to describe the planning, process, strategy, supporting and inhibiting aspects, and evaluation to improve the quality of learning through the development of arts and culture-based creativity Methods This study used a qualitative approach with multiple types of cases, its location in the SMP 2 Ngunut and MTsN Ariyojeding Rejotangan, the data in this study are primary and secondary data, engineering data collection by observation or participant observation, in-depth interviews, and documentation. From these results the authors concluded that: (1) Syllabus and lesson plans, which are prepared each semester by the subject teachers of art and culture. (2) Processes in the two institutions are also equally divided into two, with the delivery of content and practice, which in this case were similarly associated with the environment, in order to increase students’ interest and creativity. (3) Pay attention to the material compliance strategy, timing and conditions of the students at that time. (4) Supporting aspects (proper purpose, teachers are creative, active students and spirit, facilities and infrastructure adequate, and the environmental conditions that support time), and the inhibiting aspects (related to the students’ attitude sometimes crowded during the learning process and disturb her during the learning process). (5) Evaluation used in these two institutions, namely: evaluation practice, writing and oral.